2007
DOI: 10.1637/0005-2086(2007)51[614:poasdi]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of a Septicemia Disease in the Crested Ibis (Nipponia nippon) in China

Abstract: This study investigated six cases of septicemia in young crested ibises (Nipponia nippon). These birds all died with similar clinical signs, including sudden death, anorexia, diarrhea, and lameness. Immediately after death, the birds were necropsied; a blood sample was taken from heart and tissues were sampled from liver, lung, spleen, peritoneal mucus, and feces for bacteriologic examination. Anatomic observation showed that the main findings common to the sick birds were arthrocele, associated with congestio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…In recent years, there has been an increasing number of reports regarding infectious diseases in the crested ibis, including septicemia6, new castle2, Salmonella infection8, Escherichia coli infection5, avian influenza7, and others, which implies that this rare bird is at increasingly high risk under variable pathogen pressures. Identification of defensin genes responsive to certain pathogens has been conducted in many avian studies1234 but never in crested ibis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there has been an increasing number of reports regarding infectious diseases in the crested ibis, including septicemia6, new castle2, Salmonella infection8, Escherichia coli infection5, avian influenza7, and others, which implies that this rare bird is at increasingly high risk under variable pathogen pressures. Identification of defensin genes responsive to certain pathogens has been conducted in many avian studies1234 but never in crested ibis.…”
Section: Discussionmentioning
confidence: 99%
“…However, as a bottlenecked species with intensive inbreeding, recent populations suffer from low genetic diversity3. The mortality of ibis embryos and nestlings is also high145, and many pathogens can fatally infect the bird2678. Therefore, the genetic conservation and immunological function of the crested ibis require rigorous investigation.…”
mentioning
confidence: 99%
“…By analyzing the genomes of 57 historic and 8 modern samples, a recent study revealed ancestral loss of genetic variation and high deleterious mutation owing to genetic drift and inbreeding depression in current populations [32]. There have been a growing number of reports regarding various infections [33,34,35,36] and high mortality [29,33] in this bird, indicating frequent threats from pathogens and undetermined fitness. However, there has not yet been any large-scale genetic assessment on Nini populations.…”
Section: Introductionmentioning
confidence: 99%
“…This low genetic diversity could increase susceptibility for infectious diseases. According to previous studies, the recovered crested ibis population was vulnerable to Escherichia coli septicemia due to its low level of divergence of major histocompatibility complex alleles (Xi et al, 2007;Zhang et al, 2006). For this reason, multilateral and continuous pathogen monitoring for the crested ibis is needed for effective species recovery.…”
Section: Strain Tbs-100mentioning
confidence: 99%